Comparative investigation of biological indices and biochemical compounds of reproductive indicators in male and female Pangasius nasutus - DONALD TORSABO; GABRIEL AROME ATAGUBA; BENEDICT TERKULA IBER; NOORDIYANA MAT NOORDIN; NURIZZATI IDRIS; IVAN CHONG CHU KOH; MUHAMMAD YAZED ABDUH; RUMEAIDA MAT PIAH; AMBOK BOLONG ABOL-MUNAFI (Society for Indonesian Biodiversity, 2024)
Abstract. Torsabo D, Ataguba GA, Iber BT, Noordin NM, Idris N, Koh ICC, Abduh MY, Piah RM, Abol-Munafi AB. 2024. Comparative investigation of biological indices and biochemical compounds of reproductive indicators in male and female Pangasius nasutus. Biodiversitas 25: 3105-3115. Pangasius nasutus (Bleeker, 1863) is an emerging freshwater aquaculture species with known difficulties in the aspect of reproduction in captivity. This study examined biological, biochemical, and fatty acid profiles of P. nasutus obtained from cage culture systems in Pahang, Malaysia as indicators of sexual maturity. A total of 73 samples (43 females and 30 males) of fish were used to collect data on biological indices, biochemical composition, and fatty acid percentages. Otolith growth marks were examined and counted under a microscope for age determination. The results showed a female to male sex ratio of 1.5:1 and the age structure skewed towards three years old fish. The Gonadosomatic Index (GSI) was significantly high for females and with a significantly low difference in the Coelomic Fat Index (CFI) in comparison with the males. Protein and lipid were found to be highest in the testes of males and the liver of females respectively. Saturated Fatty Acids (SFA) and Monounsaturated Fatty Acids (MUFA) significantly differ between males and females in the liver and gonads, in addition to highest Polyunsaturated Fatty Acids (PUFA) also recorded in the gonads of 3 years fish. The current study reveals that P. nasutus reaches sexual maturity at a minimum age of 3 years, with an average body weight of 1099.27±21.5 g and an average total length of 48.36±0.45 cm. Significant differences between fatty acid groups highlight the need for lipid nutrition in the broodstock of P. nasutus for the supply of adequate energy and essential fatty acids for their gonad development.